Patient misadventures caused by prescribing errors detected at a Brazilian community pharmacy - Marianne Silveira Camargo; Sóstenes Mistro (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2022)
Background: Efforts to reduce medication errors in healthcare have been widespread around the world with the aim to improve the quality of care. Failures observed at the prescription phase are reported as being the most prevalent preventable errors. Adverse events related to inappropriate prescriptions are an important threat to patient safety. In this context, a community pharmacist is in a strategic position to evaluate, detect, and correct problems that may have occurred during prescribing. Consequently, this reduces the risk of negative clinical and economic outcomes. Objective: To identify the consequences of prescription errors that impede drug dispensing at a Brazilian community pharmacy from the perspective of patients. Method: Cohort study, with no comparison group, in a Brazilian community pharmacy, which included patients with prescription errors, which made it impossible for correct drug dispensing. Patients were interviewed at the time of problem detection and followed up until an outcome was reached. Results: Of the 32 interviewed patients, 23 (71.9%) reported some harm to their health due to a delay in starting treatment, and 19 (59.4%) experienced extra expenses due to medication not being dispensed. Conclusion: Prescription errors that preclude the dispensing of any medication can lead to negative clinical outcomes and a financial loss to patients.